A Comparative Study of Acceptance and Commitment–Based Couple Therapy and Integrative Behavioral Couple Therapy on Marital Adjustment and Altruism in Couples with a Child with a Disability - Ghasemi, Abbas; Molazadeh, Alireza; Hamidipour, Rahim (KMAN Counseling & Psychology Nexus, 2026)
The objective of the present study was to compare the effectiveness of Acceptance and Commitment–Based Couple Therapy and Integrative Behavioral Couple Therapy on altruistic behavior and marital adjustment in couples. This study was applied in nature and employed a quasi-experimental pretest–posttest design with a control group. The statistical population consisted of married couples who met the study inclusion criteria, from whom 30 couples were selected using convenience sampling and randomly assigned to two experimental groups and one control group. The experimental groups received Acceptance and Commitment–Based Couple Therapy or Integrative Behavioral Couple Therapy according to structured intervention protocols, while the control group received no intervention. Data were collected using standardized measures of altruistic behavior and marital adjustment at pretest and posttest stages. Data analysis was conducted using analysis of covariance (ANCOVA) to compare posttest outcomes while controlling for pretest scores. The inferential results of the ANCOVA indicated that both Acceptance and Commitment–Based Couple Therapy and Integrative Behavioral Couple Therapy led to statistically significant improvements in altruistic behavior and marital adjustment compared with the control group (p < .001). After controlling for baseline scores, group membership had a significant effect on posttest altruism and marital adjustment, with very large effect sizes. However, no statistically significant difference was found between the two experimental groups, indicating that both therapeutic approaches were similarly effective in enhancing altruism and marital adjustment. The findings suggest that both Acceptance and Commitment–Based Couple Therapy and Integrative Behavioral Couple Therapy are effective interventions for improving altruistic behavior and marital adjustment, and either approach can be confidently used in clinical couple therapy settings to promote relational functioning.